ANALISIS TINGKAT USABILITAS DAN USER EXPERIENCE PRESENSI GURU DAN STAFF SD ANGKASA 1 KAB. MAROS DENGAN METODE USE QUESTIONNAIRE DAN UEQ QUESTIONNAIRE PENDEKATAN PARTISIPATORIS - Andi Haslindah; Ahmad Hanafie; Sri Mutiara (ILTEK : Jurnal Teknologi, 2026)
Measuring the effectiveness of an attendance system requires a scientific approach to obtain valid and accurate data. Instruments such as the Usability Questionnaire assess the ease and efficiency of use of the application by teachers and school staff. This study aims to determine the level of usability of the digital attendance system used by teachers and staff of SD Angkasa 1, Maros Regency based on the results of the Use Questionnaire evaluation, determine the level of user experience of the digital attendance application based on the results of the User Experience Questionnaire (UEQ) measurement, and compile recommendations for improving the digital attendance system based on the results of the usability analysis and user experience with a participatory approach. The research method used is a quantitative method with an evaluative approach. Data were collected by distributing questionnaires to 20 respondents consisting of teachers and staff of SD Angkasa 1, Maros Regency. The research instrument used the USE Questionnaire to measure the level of usability and the User Experience Questionnaire (UEQ) to measure user experience of the digital attendance system. The results showed that the level of usability of the digital attendance system obtained an average value of 4.25 which is in the very good category. In detail, the learnability aspect obtained a value of 4.17, efficiency 4.30, memorability 4.35, error 3.95, and satisfaction 4.46. Meanwhile, the UEQ measurement results indicate that the user experience ranges from neutral to slightly positive, with the highest score for novelty at 0.125, followed by efficiency at 0.050, and dependability at 0.013. However, several aspects still received low scores, such as attractiveness (-0.08) and perspicacity (-0.03), indicating a need for improvements in the system's appearance and ease of understanding.